1995
DOI: 10.1055/s-2007-1005764
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Features of Helicobacter pylori-Related Gastritis

Abstract: We conclude that it is not possible to diagnose Hp-related gastritis on the basis of the endoscopic appearance alone. The diagnosis should be based on other criteria, such as a rapid urease test, or a histological examination of gastric biopsies, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 0 publications
0
61
1
3
Order By: Relevance
“…According to the literature, the antral nodularity is significantly associated with chronic active gastritis and follicular gastritis and showed high specificity (98.5%) and high positive predictive value (91.7%) but low sensitivity (32%) for the diagnosis of HP [8,20] . In this research these images shown to be 89.2 times more frequent in infected individuals (OR = 89.26 and 95% CI = 5.19 -153) demonstrating that this finding is valuable in the diagnosis of HP infection and the endoscopic finding that best showed this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, the antral nodularity is significantly associated with chronic active gastritis and follicular gastritis and showed high specificity (98.5%) and high positive predictive value (91.7%) but low sensitivity (32%) for the diagnosis of HP [8,20] . In this research these images shown to be 89.2 times more frequent in infected individuals (OR = 89.26 and 95% CI = 5.19 -153) demonstrating that this finding is valuable in the diagnosis of HP infection and the endoscopic finding that best showed this association.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports in the literature regarding endoscopic patterns of related HP gastritis using conventional endoscopy. In the initial works in 1995, some authors concluded that it was not possible to establish this diagnosis based only on endoscopy [8,9] . However, newer technologies such as magnification and chromo endoscopy [11,12] have shown that there are endoscopic features that are clearly associated with HP infection, while other endoscopic features are related to non-infected cases or cases in which the infection has already been eradicated [10] .…”
Section: Introductionmentioning
confidence: 99%
“…No consensus evidence has been reached as to whether chronic gastritis related to H. pylori infection can be diagnosed from macroscopic features alone in gastric mucosa (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Nodular gastritis, however, is characterized endoscopically by micronodules with a smooth surface and is associated with pediatric patients with H. pylori infection (4,34).…”
Section: Discussionmentioning
confidence: 99%
“…The gastroscopic findings of H. pylori infected gastric mucosa were erythema, erosions, antral nodularity, thickened gastric folds, and visible submucosal vessels. However, these findings are not a reliable method of diagnosis because of their low sensitivity and specificity (Laine et al, 1995;Bah et al, 1995;Mihara et al, 1999;Redeen S et al, 2003). In 2010, Taiwanese endoscopist a study using close-up observation between the endoscope tip and the gastric mucosa and found the "mosaic pattern" in the corpus mucosa.…”
Section: Introductionmentioning
confidence: 99%